Revised Checklist of Powdery Mildews (Fungi: Erysiphales) from Nepal - Adhikari, M. K. (Journal of Plant Resources, 2022)
The mycotaxa belonging to Erysiphales reported from Nepal since 1966, are revised based on 20 published papers. The recent moleculer and phyllogenetic analysis have done several changes in the nomenclature of several powdery mildew species reported earlier from Nepal. Some were erroneously reported, while some species have undergone synonyms. Near about eighteen species of Oidium (anamorphic: imperfect stage) reported earlier still need collections, examination and study are not incorporated here. The present checklist provides corrections to misidentified species with their current (authentic) or valid names and some additons have been made based on publications. The list also records three endemic species. So, the revision includes 13 genera and 53 species parasitic on 76 flowering plants gathered from different areas of Nepalese Himalayan belt.